(3GdSjGSI hGdCMcGes - (3OOg CafOj, eMeO OOg Hf eUWai Hf MHjH, J (B1146 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi SjOfG eMeO hBdg hUMHg CLeYjf PcQ aj GdYfGjI TQM GdgOGjI JZdjX LRGA dgG Mce TQYj MSeG deGOI GdaSGO hPcQ aj eYfi GdMcGe GdSjGSI TQYjI eZdXI Ke bGd GdSjGSI fhYGf s
(3BNQgG (B:s
(3hdh Yde Cfge dG jbJdhf efg (B( (3cPG (B) (3hdG jNGahf efg VQHG hTJeG agh HGdNjGQ hGdCeQ HGdeYQha hGLH Ch aQV EPG ZdH Ydi Xf GdCeQ Cfg dh CeQg HGdeYQha fRd GdaSb hEf ZdH Ydi Xfg Cfg dG JQc (B( (3cPG (B) (3dG jchf EKeG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3 / 286s
(3EjVGM Gdecfhf (B2 / 304s
(3gOjI GdYGQajf (B2 / 321s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3Gdabg GdMfHdjs